A New Decision Making Model for Subcontractor Selection and Its Order Allocation. Issue 1 (February 2014) - Abbasianjahromi, Hamidreza; Rajaie, Hossein; Shakeri, Eghbal; Chokan, Farzad
ABSTRACT All experts agree on the importance of subcontracting. The high impact of subcontractors on the construction process means that the selection of subcontractors is a sensitive activity. Previous investigations documented the selection of subcontractors based on criteria but did not consider the number of subcontracted tasks. This paper explores allocating the best portion of tasks to subcontractors while optimizing the risk and cost in the fixed project schedule. The study's main finding demonstrates that subcontractor selection without attention to the order allocation is not a realistic approach; therefore, a hybrid model that applies continuous ant colony and fuzzy set theory is proposed.